Faktor yang Berhubungan dengan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Abeli Kota Kendari Tahun 2023 - Lina Yanti; Ruwiah Ruwiah; Paridah Paridah (KOLONI, 2023)
Stunting is a condition of failure to thrive in children under five years of age (toddlers) which is caused by chronic malnutrition and recurrent infections, especially in the first 1,000 days of life (HPK), namely from the fetus to the child aged 23 months. This research aims to determine the factors associated with the incidence of stunting among toddlers in the Abeli ​​Health Center Working Area, Kendari City in 2023. The type of research used is quantitative research with a cross-sectional research design. This research used a proportional random sampling technique with a sample size of 90 respondents. Data analysis used univariate and bivariate analysis using the chi-square test. The research results were obtained. The results of statistical tests using the chi-square test showed that there was no relationship between maternal knowledge and the incidence of stunting with a value (p = >0.05), there was no relationship between family income and the incidence of stunting with a value (p = >0.05 ), there is a relationship between the history of exclusive breastfeeding and the incidence of stunting (p = <0.05) and there is a relationship between nutritional status and the incidence of stunting with value (p = <0.05). The conclusion in this study is that the factors related to the incidence of stunting among toddlers in the Abeli ​​Health Center Working Area, Kendari City are exclusive breastfeeding and nutritional status. The suggestion given by the researcher to the community health center is that the community health center staff, especially the community health center nutritionist, provide counseling regarding stunting and go directly to the community to provide education on food ingredients and a good menu schedule for toddlers.